(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to determine the effectiveness of an educational program based on some cognitive load strategies in fifth grade literary students’ acquisition of historical concepts To achieve the goal and hypothesis of the research, two approaches were followed, the first a descriptive approach to construct the educational program, and the second an experimental approach to verify its effectiveness, and a number of procedures that include determining the experimental design, and the research community, which was limited to fifth grade literary students who study the subject of modern and contemporary European and American history in schools. Preparatory and secondary (day) affiliated with the General Directorate of Education of Baghdad Governorate/Al-Rusafa I. As for the research sample, it amounted to (88) students distributed equally into two groups (experimental and control), with (44) students in each group, chosen randomly from the class students. The fifth literary group is studying the modern and contemporary history of Europe and America at Abdullah bin Rawahah Preparatory School, in the Sumer neighborhood located in the Al-Shaab area of the General Directorate of Education in Baghdad, Al-Rusafa II, after conducting equivalence operations in academic achievement for the previous year, intelligence scores, and chronological age. To achieve the goal of the research, a test for acquiring historical concepts was constructed, consisting of (45) multiple-choice items, and its apparent validity was extracted by presenting it to experts and arbitrators, in addition to extracting its stability and discriminating power. After correcting the answers and processing the data statistically, the results showed the superiority of the students of the experimental group who studied the subject of modern and contemporary American and European history according to the educational program over the students of the control group who studied the same subject according to the usual method in the posttest of concept acquisition. In light of the results of the research, it was done. Reaching a number of conclusions, recommendations and proposals that would develop the teaching of history in the middle school.